(Weak) Pre-L-ideals and Atoms in L-algebras - Romano, Daniel Abraham (Sarajevo Journal of Mathematics, 2025)
The notion of L-algebras was introduced in 2008 by W. Rump. He also introduced the concept of L-ideals in this class of logical algebras. This paper introduces the concept of (weak) pre-L-ideals and atoms in L-algebras and discusses some of their important properties. A connection has been established between pre-L-ideals and atoms in L-algebras.